If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(20x + -3) + -1log(x + 4) = 2 Reorder the terms: glo(-3 + 20x) + -1log(x + 4) = 2 (-3 * glo + 20x * glo) + -1log(x + 4) = 2 (-3glo + 20glox) + -1log(x + 4) = 2 Reorder the terms: -3glo + 20glox + -1glo(4 + x) = 2 -3glo + 20glox + (4 * -1glo + x * -1glo) = 2 -3glo + 20glox + (-4glo + -1glox) = 2 Reorder the terms: -3glo + -4glo + 20glox + -1glox = 2 Combine like terms: -3glo + -4glo = -7glo -7glo + 20glox + -1glox = 2 Combine like terms: 20glox + -1glox = 19glox -7glo + 19glox = 2 Solving -7glo + 19glox = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + -7glo + 19glox = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -7glo + 19glox = 0 The solution to this equation could not be determined.
| 82=2+30+40a | | 0=b^2+b | | 28s-26=40s-2(2s+5) | | 1m+6=7m | | 4x^2-12x=12 | | 1/4(b+2)=10 | | -3x=-2x+3 | | .25y-.6=.15y+3-.8y | | 2xy-7y=49 | | 5+0.02x=4.69+0.08x | | 1400=10x+500 | | 45=-15+5g | | 2(2m-1)+6(m+2)=8m | | 5f+10=6-3f | | 3s-2=1 | | (x-4)=(2x-7) | | -3k-6=-4k-11 | | 5ng-5n+10ng-20n= | | 0.5x+2x=-50 | | -9+p=-11 | | 8k+3-2k=6 | | 9-8m=-8(m-2) | | 44.79=9g+3.84 | | 23x+33=13x+39 | | 3(2t-1)-7=4(t+1) | | 30-5x=50-13x | | 1.48g-9=0.62 | | x(50-2x)(30-2x)=4104 | | -7-9(n+4)=9-7(n+4) | | 76-2x=90-3x | | -5.3(4p+6)-2.9(2p-5)= | | Uw+un=xforu |